النمذجة الحاسوبية لمخفضات علب السرعة المخصصة لمحاور الآليات الكبيرة وتحليلها بمساعدة العناصر المنتهية - إسبر منذر (Latakia University Journal -Engineering Sciences Series, 2017)
إن استخدام المنهجيات والتقنيات الحديثة كنهج جديد لتقييم عملية التصاميم الهندسية في الصناعة دفع إلى استخدامها في تقييم تصميم علب السرعة في الآليات الكبيرة . إن علبة السرعة المصممة خصيصا للآليات الكبيرة العاملة في ظروف القيادة على الطرق الوعرة تحتاج إلى محور قنطري portal axle يتم تثبيته بين العجلة وعمود المحور بهدف إعطاءه ارتفاعاً إضافياً للآلية عن الأرض. في هذه الدراسة، سوف يتم تحليل المحور القنطري باستخدام طريقة العناصر المنتهية (FEM). وسينفذ ذلك على ثلاثة مجموعات مختلفة لنظام المسننات المعشقة التي يجري تحليلها وهي : المسننات المعشقة بدون مسنن وسيط, مع مسنن وسيط واحد, ومع مسننين وسيطين. كما يتم محاكاة تحليل الإجهاد الساكن لـ FEM على ثلاث مجموعات مسننة معشقة مختلفة لدراسة إجهاد انحناء الأسنان وسلوك إجهاد الاحتكاك للمسننات المعشقة في مواقع زاوية مختلفة تتراوح من °0 الى °18 درجة. The use of modern methodologies and techniques a new approach to evaluate the process of engineering design in the industry pay to use in evaluating the speed in large cans mechanisms design. The gearbox that is designed for big vehicles for off-road driving conditions need portal axle which installed between the wheel and the axle shaft to give higher ground clearance to the vehicle. The modeling and simulation of spur gear which contacted with portal axle is important to predict the actual motion behavior, but it’s so complicated to study. In this study, it’ll analysis the portal axle by using finite element method (FEM), modal analysis will simulated on three different combinations of gear train system, the three gear trains being analyzed are: gear train without idler gear, one idler gear and two idler gears. FEM static stress analysis will also simulated on three different gear train to study the gear teeth bending stress and contact stress behavior of the gear trains in different angular positions from °0 to °18 degree.